The Christian-Muslim frontier : a zone of contact, conflict, or cooperation - Apostolov, Mario (RoutledgeCurzon, 2004)
An examination of the civilisational interface between Christianity and Islam from the unique perspective as a zone of contact rather than a distinct boundary.
Keywords: Islam -- Relations -- Christianity.; Christianity and other religions -- Islam.; International relations.; Security, International.; Islam -- Relations -- Christianisme.; Christianisme -- Relations -- Islam.; Relations internationales.; international relations.; 11.07 relations between religions.; POLITICAL SCIENCE -- Globalization.; Christianity; Interfaith relations; International relations; Islam; Security, International; Christentum; Islam.; Christendom.; Interreligieuze dialoog.